Urogynaecological complications in pregnancy. Issue 2 (February 2021) - Kashif, Uzma; Riaz, Nadia; Ramasubramanian, Swapna Percholli; Iles, David
Abstract: Obstetricians should remain aware of physiological adaptations that the urinary tract undergoes in pregnancy. This altered physiology makes pregnant women susceptible to increased risk of urological complications such as acute infection and urinary retention. Close anatomical proximity between gynaecological and urinary system makes the urinary bladder and ureters prone to iatrogenic injury during caesarean section, and this may result in long term sequalae. This review article provides an overview of presentation and management of common Urogynaecological conditions that may be encountered in pregnancy.